Workplace Segregation and the Labour Market Performance of Immigrants - Sébastien Willis (Center for Economic Studies and ifo Institute (CESifo), 2022)
Immigrants are more likely to have conationals as colleagues, however the consequences of such workplace segregation is an open question. I study the effect of the conational share in an immigrant's first job on subsequent labour market outcomes using register data from Germany. I instrument for the conational share using hiring trends in the local labour market and find that a ten-percentage-point increase in the initial conational share lowers employment rates by 3.1 percentage points six or more years after the start of the first job, an effect not observed for non-conational immigrants, with no effect on wages conditional on employment. The employment effect appears to be due to the effect of differences in the composition of social networks induced by differences in the initial workplace on subsequent job search behaviour, although differential Germany-specific human capital acquisition cannot be entirely ruled out.
Keywords: J61; J64; J31; 330; employment; segregation; coworker networks; immigrant earnings dynamics